AN ANALYSIS FOR MODE CHOICE PREFERENCES BETWEEN ANKARA AND ISTANBUL - Gursoy, Mustafa; Kusakci Gundogar, Sumeyya Seyma; Tanriverdi, Sami Cankat; Alcura, Guzin Akyildiz (YILDIZ TECHNICAL UNIV, 2020)
In this study we conduct a survey which asks the respondents to evaluate the transportation modes based on trip time, trip cost, comfort, reliability variables whether they use or not the mode. It is assumed that the choices made based on utility theory and Multinomial Logit Model (MLM) incorporated. Utility functions for all modes (air, intercity bus, rail and private car) that serve between Ankara and Istanbul incorporated to the model presented. The weights of variables that effects choice probabilities used in utility function are calculated and then aimed modal distributions with required probability expressions. Finally modal distribution percentages are calculated for HSR (High Speed Rail System) in-operation as well as other three modes. Calculated modal distribution percentages are 51,91 % for intercity bus, 20,70 % for private car, 19,96 % for air and 7,43 % for HSR. With this study, we aimed that decision makers will be able to make more realistic projections and to develop a useful tool to help them made best possible transportation investments. Also a contribution for the related literature via a case-study is another aim of this work.
Keywords: High speed rail; transportation mode choice; modal distribution; transportation planning; transportation modelling; HIGH-SPEED RAIL; TRAIN; Engineering